Improving Elementary School Students' Learning Outcomes Using the Project Based Learning (PJBL) Model - Nur Fatimah (Molang: Journal Islamic Education, 2026)
Classroom Action Research (CAR) was motivated by the results of science learning on the water cycle material for VA class students at SDN Beji 01 Batu which had not yet reached the minimum completeness criteria (KKM). This study aims to improve Natural Science learning outcomes on the water cycle material using a project-based learning model with a project to make a simple water purification tool for VA class students at SDN Beji 01, Batu Regency, in the 2025/2026 school year. Researchers carried out PTK in two cycles and each cycle was carried out in two meetings. The results of the research on the pre-cycle action which had classical completeness of 21.73% with an average value of 53 experienced an increase in the first cycle of action. In the first cycle the classical completeness reached 69.56% and an average value of 77. The research ended in cycle II achieving completeness classical 95.65% and average value 80. Based on the results of this study it can be concluded that the application of the Project Based Learning model can improve science learning outcomes on the water cycle material in class V students at SDN Beji 01 Batu in the 2025/2026 academic year.